Expanding nurse practice in COPD: is it key to providing high quality, effective and safe patient care? - Fletcher, Monica J (Prim Care Respir J, 2013)
The prevalence of chronic obstructive pulmonary disease (COPD), a common and preventable chronic disease, is on the increase, and so are the financial and social burdens associated with it. The management of COPD is particularly challenging, as patients have complex health and social needs requiring life-long monitoring and treatment. In order to address these issues and reduce the burden imposed by COPD, the development of innovative disease management models is vital. Nurses are in a key position to assume a leading role in the management of COPD since they frequently represent the first point of contact for patients and are involved in all stages of care. Although evidence is still limited, an increasing number of studies have suggested that nurse-led consultations and interventions for the management of COPD have the potential to impact positively on the health and quality of life of patients. The role of nurses in the management of COPD around the world could be significantly expanded and strengthened. Providing adequate educational opportunities and support to nurses, as well as addressing funding issues and system barriers and recognising the importance of the expanding roles of nurses, is vital to the well-being of patients with long-term medical conditions such as COPD and to society as a whole, in order to reduce the burden of this disease.